2004
DOI: 10.1086/423388
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Resistance in HIV‐1–Infected Patients with Persistently Detectable Low‐Level Viremia while Receiving Highly Active Antiretroviral Therapy

Abstract: The finding that clinically significant resistance mutations were present in some but not all patients with persistent viremia (range, 50-400 copies/mL) highlights the need to improve the sensitivity of current clinical assays for detection of drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 24 publications
1
51
0
2
Order By: Relevance
“…(i) Antiretroviral resistance increases with persistent LLV. ARV drug resistance is well documented in patients with a viremia level of Ͻ1,000 cpm (Table 4), though the reported prevalence varies depending on ART experience, virological suppression/failure, duration of viremia, and treatment regimen (45,(68)(69)(70)(71)(72)(73)(74)(75). In one of the largest studies (n ϭ 1,001), genotyping of clinical samples between 1999 and 2006 in the United Kingdom revealed at least one drug resistance mutation (DRM) in 60% and 72% of samples, with pVLs of Ͻ300 cpm and 300 to 999 cpm, respectively (70).…”
Section: Figmentioning
confidence: 99%
“…(i) Antiretroviral resistance increases with persistent LLV. ARV drug resistance is well documented in patients with a viremia level of Ͻ1,000 cpm (Table 4), though the reported prevalence varies depending on ART experience, virological suppression/failure, duration of viremia, and treatment regimen (45,(68)(69)(70)(71)(72)(73)(74)(75). In one of the largest studies (n ϭ 1,001), genotyping of clinical samples between 1999 and 2006 in the United Kingdom revealed at least one drug resistance mutation (DRM) in 60% and 72% of samples, with pVLs of Ͻ300 cpm and 300 to 999 cpm, respectively (70).…”
Section: Figmentioning
confidence: 99%
“…For multidrug-resistant variants to emerge during ART, either viral variants with multiple drug resistance mutations that exist prior to therapy must be selected during treatment or ongoing, low-level virus replication and recombination must allow the necessary multiple mutations to accumulate on single viral genomes. Many studies have demonstrated that suboptimal therapy results in the selection of drug-resistant variants as a consequence of incomplete viral suppression (15,17,21,24,32,33,42). For example, the widespread and rapid resistance to monotherapy and dual-drug combination therapy (6,13,16,19,25,30,35,37,41) and the emergence of nonnucleoside reverse transcriptase (RT) inhibitor (NNRTI) resistance mutations after single-dose nevirapine to prevent mother-to-child transmission of HIV during childbirth in resource-limited settings (12,20,26) support the hypothesis that preexisting resistance and ongoing replication during suboptimal treatment result in the selection of drug-resistant virus and virologic failure.…”
mentioning
confidence: 99%
“…Commercial assays require Ն1,000 copies/ml, but noncommercial, modified commercial, and proprietary GART assays have successfully detected resistance at much lower levels (1,3,4,(6)(7)(8). Since 2001, the Infectious Diseases Laboratory at the Veterans Affairs Medical Center in Washington, D.C., has performed genotypic testing using the TruGene HIV type 1 (HIV-1) genotyping kit/OpenGene DNA sequencing system (Bayer HealthCare LLC, Tarrytown, NY).…”
mentioning
confidence: 99%